Trans-Umbilical Open Port Placement During Laparoscopic Access: A Safe Technique - Sarder, Md Atiqul Haque; Ahmed, Quazi Sabran Uddin (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Intra-peritoneal access and creation of pneumoperitoneum through a quick, safe and reliable technique is important for Laparoscopic Surgery. Specially in an resource constrained setting where there is paucity of needed equipment and cost is prohibitive, utilization of the fewer instruments available and accompanid by excellent functional and cosmetic outcomes should be the aim of a laparoscopic surgeon. Objectives: To describe a modified method of primary trocar introduction that utelizes fewer available instruments. Materials and Methods: A vertical incision is made in the trans-umblical region at the base of to an everted umblicul scar. The linea alba is incised and the resultant opening bluntly developed after which the 1st port is inserted using tocar as an guide. The trocar is withdrawn while the canula is pushed in. Results: We included total 124 patient (Male-44, Female-80) in the study period, from Jan 2017 to December 2018. In one single surgical unit, with the age limit 18-75 years, With no significant complications. Conclusion: This modified open trans-umblical approach is a simple, quick, and reliable way to primary port insertion. Access is gained easily in different age groups and umblicus types, through a small congenital umblical defect that is almost universally present. It is associated with minimum morbidity and has excellent outcome. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 67-70